A note on Kathani cattle qualitative body characteristics - RL Bhagat; VY Deshpande; PK Singh; MS Tantia (Journal of Livestock Biodiversity, 2025)
Kathani cattle is an unexplored population of Vidarbha region of Maharashtra. The information on physical traits of 9474 Kathani animals from Vidarbha region of Eastern Maharashtra state were collected. The white coat color pattern was the highest (67.09%) in Kathani animals followed by reddish (29.14%) and blackish (3.77%). Most of the animals (64.30%) are of white skin colored followed by reddish blackish and kosa- a combination of black and white. Muzzle, horns and hooves are black in almost all of the Kathani cattel. Horns are either straight or curved. Forehead is straight. Poll is non- prominent mostly. Hump is either medium or small in size. Dewlap is medium in most of the animals. These physical traits may be helpful in developing the breed descriptors of Kathani cattle for registration as a cattle breed of India.